(Invited) Non-Aqueous Atomic Layer Deposition of SnO2 for Gas Sensing Application. (20th July 2018) - Marichy, Catherine; Silva, Ricardo Manuel; Pinna, Nicola; Willinger, Marc; Donato, Nicola; Neri, Giovanni
Abstract : Tin dioxide thin films are grown at low-moderate temperature using a non-hydrolytic atomic layer deposition process. Granular SnO2 thin films are obtained from tin(IV) tetra-butoxide reacting with acetic acid, at temperatures as low as 75 °C. Influence of pulse length of both reactants and of the deposition temperature on the saturation is studied. A narrow ALD window is established between 150 and 175 °C with a growth per cycle of 0.07 nm and with a linear growth as a function of the number of cycles. Above 200 °C decomposition of the tin precursor is not negligible. Microstructure and morphology of the as-prepared films as well as the influence of the deposition parameters are investigated using electron and atomic force microscopies. The band gap of the obtained films is determined using UV-visible spectroscopy. Finally the use of the SnO2 coated carbon nanotubes as gas sensing layer is discussed.